Sacrifice in Judaism, Christianity, and Islam - Weddle, David L. (David Leroy), 1942- (Book collections on Project MUSE., 2017)
In the book of Genesis, God tests the faith of the Hebrew patriarch Abraham by demanding that he sacrifice the life of his beloved son, Isaac. Bound by common admiration for Abraham, the religious traditions of Judaism, Christianity, and Islam also promote the practice of giving up human and natural goods to attain religious ideals. Each tradition negotiates the moral dilemmas posed by Abraham's story in different ways, while retaining the willingness to perform sacrifice as an identifying mark of religious commitment. This book considers the way in which Jews, Christians, and Muslims refer to 'sacrifice' - not only as ritual offerings, but also as the donation of goods, discipline, suffering, and martyrdom. Weddle highlights objections to sacrifice within these traditions as well, presenting voices of dissent and protest in the name of ethical duty.